The " dejudicialization" policy as a mechanism for ensuring the access to justice and the human right to housing - Freire Menezes, Brenno Augusto; Rocha Cavalcanti, Ana Claudia; Miranda de Souza, Flávio Antonio; de Vasconcelos Bezerra, JoÃ£o Manoel (Ius Humani. Jornal do direito, 2025)
This study aims to present arguments capable of defending the possibility of using extrajudicial mechanisms to resolve possessory conflicts, in order to effectively guarantee the human right to housing, especially for marginalized populations. Throughout this research, the adoption of dejudicialization by the Court of Justice of Pernambuco in the resolution of possessory actions will be analyzed, and how this tool can function as an excellent mechanism to reduce the overload faced by the Judiciary in the instruction and processing of possessory actions. In order to achieve the main objective of this study, theoretical data obtained through bibliographic and documentary research will be presented, using qualitative methodology and the hypothetical-deductive method, reaching, in the end, the conclusion that it is necessary to rethink, review and reformulate the existing mechanisms of access to justice as a tool for the realization of human rights, especially the human right to decent housing.